Adsorption performance of activated carbon for methane with low concentration at atmospheric pressure. Issue 11 (3rd June 2021) - Song, Yueqin; Zhou, Xiaolong; Wang, Jin An
ABSTRACT: This work reports a novel method of combining both chemical activation and N2 or steam post-treatment at high temperature for producing activated carbon (denoted as AC) used for the selective adsorption and separation of methane from the coal-bed gases. The used AC in the investigation mainly contained three kinds, commercial activated carbon (denoted as GH-8), the prepared activated carbon, denoted as AC-P, and AC-K, which was prepared by chemical activation using phosphoric acid and potassium hydroxide solution, respectively. Textural properties, surface oxygen-containing functional groups and methane adsorption performances of AC-P, AC-K, and GH-8 samples were comparatively investigated. Results demonstrated that both AC-P and AC-K showed higher methane adsorption capacity than the commercial activated carbon sample GH-8. Steaming treatment to AC-P at 800°C significantly enhanced the methane adsorption capacity to 6.5 mg/g, which was approximately two times higher than the commercial sample GH-8 (3.2 mg/g). The pronounced increment of adsorption capacity over AC-PS800 from steam-treatment was attributed to the significant increase of the area of micropores with a pore diameter of 0.45–0.65 nm. The presence of surface oxygen-containing groups on AC was proven to be slightly unfavorable to methane adsorption. CH4 concentration in desorbed gas from AC-PS800 was drastically improved to about 70% in the effluent from about 5% in the feed gas, which demonstrated that the prepared AC-PS800 possessed high selective adsorption capacity for methane. These results would pay the way for concentrating and future utilization of methane in coal-bed gas.